First time description of dismantling phenomenon - Barrer, Laurence; Gimenez, Guy (Frontiers in Psychology, 2015)
Dismantling is a complex psychic phenomenon, which is not easy to define, and little interest has been shown in the subject. The authors of this paper want to demonstrate that dismantling is the main defence mechanism in autism, bringing about de-consensus of senses. The effects perceived in a child with autistic disorder are passivity and lack of thought. The authors' purpose here is to define the dismantled state and reveal its underlying process. This paper will therefore describe for the first time in literature, the dismantling phenomenon and will submit a metapsychological approach of this defence mechanism.